Rapid Spectrophotometric Determination of Trace Amounts of Nitrate-Nitrogen Using Dapsone and α-Naphthol - Padmarajaiah Nagaraja; Jainara S. Prakash; Besagarahally L. Bhaskara (E-Journal of Chemistry)
A simple, rapid and sensitive spectrophotometric method has been developed for the trace determination of nitrite using Dapsone and α-Naphthol. The proposed method is based on the diazotization of Dapsone followed by coupling with α-Naphthol in sodium hydroxide medium to give an intense pink coloured azo dye. The dye shows absorption maximum at 540 nm. The molar absorptivity and Sandell’s sensitivity being 5.749 × 104 l mol-1 cm-1 and 0.24 ng cm-3 respectively. Tolerance limit for interfering ions and complexing agents were reported. Other analytical parameters and applications of the method for analysis of tap water, lake water, and industrial effluents have been investigated.